Estudo da rigidez e da resistência ao dano de misturas asfálticas com ligantes modificados por borracha e polímero - Oliveira, Andressa Ambrós de (2019)
The quality of Brazilian highways, generally constituted by asphalt concrete, is inadequate to the constant and heavy flow of vehicles that circulate daily. Because of this and considering that they are the main means of transport of cargo and passengers, the socioeconomic rise of the country is impaired, as well as the safety and comfort of the people who travel through these routes. The study of the behavior of mixtures composed of different asphalt binders is important in order to overcome the problems in the pavement, since their performance has a direct relation with the quality of the pavement. In this context, the knowledge of the stiffness of the mixture is fundamental to understand the performance of the binders on it when it is subjected to different temperatures and loading frequencies, as well as its resistance to permanent deformation and fatigue. Thus, this research aims to evaluate, through laboratory tests, the mechanical properties of mixtures caused by two modified asphaltic binders, polymer modified AMP 60/85 and Ecoflex B 3G, modified by rubber, composed of the same skeletal stone, with grain size according to the DNIT C range. The blends were dosed according to the Superpave methodology and subjected to the Resilience Module and Complex Module tests to analyze stiffness; as well as Flow Number to measure the damage to permanent deformation. Also, the Direct Tension Fatigue test was done, using the classic approach by the Wöhler curves and the S - VECD as a premise to infer the fatigue damage. In order to understand the results obtained from the Complex Modulus tests, the 2S2P1D modeling was used, since the mixtures have viscoelastic behavior. It has been found that mixtures with rubber modified binder have higher stiffness than those with polymer and both have better results than conventional CAPs for this criterion. Regarding issues of permanent deformation, the mixture with polymer supported more cycles of loading than with rubber and both presented inferior results when compared to the 50/70 REFAP binder, analyzed for being of the same State as those of this research. As for the fatigue questions, by the Nascimento (2016) method, the modified mixtures have supremacy, especially with polymer.